Job Embeddedness to Citizenship Behavior: Role of Outcome Orientation and Relationships with Peers (Journal of Organizational Psychology, 2020)
While highly embedded individuals possess disproportionate resources to retain stable status, little is known about their exchange relationships with peers (TMX), especially in an outcome-oriented workgroup climate that advocates results. Drawing on theories of conservation of resources and social exchange, we advance an explanation on why highly embedded employees are likely to form high quality TMX, and how outcome-oriented workgroup climate moderates this effect. Results from a multilevel study of 297 employees nested in 49 workgroups indicated that focal employees’ job embeddedness predicted their helping behaviors through their TMX, and these effects were stronger in a high outcome-oriented workgroup climate.
Keywords: Organizational Psychology; job embeddedness; team-member exchange; outcome orientation; conservation of resources; social exchange